1996
DOI: 10.1111/j.1467-8624.1996.tb01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes of Black Students toward School, Achievement, and Other Educational Variables

Abstract: To provide data on the perceptions and attitudes of gifted Black early adolescents toward school, achievement, and other educational variables, the responses of gifted Black students (n = 48) were compared to Black students in a regular education (n = 50) and potentially gifted program (n = 50). Results indicate that gifted Black students held significantly different attitudes and perceptions than both potentially gifted students and regular education students relative to principles of the achievement ideology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
0
51
0
1
Order By: Relevance
“…Ogbu (1978) noted that Americans are motivated to maximize school achievement because of the belief that more education leads to better jobs, higher wages, and social status. Survey-based inquiries have supported the notion that societal conditions affect individuals' achievement via perceptions about the opportunity structure (Ford and Harris 1996;Mickelson 1990). These studies have found that students who express a belief in the achievement ideology (that education leads to status attainment) experience academic success, while those who challenge this belief do not.…”
Section: Centrality Of Beliefs and The Acting White Hypothesismentioning
confidence: 99%
“…Ogbu (1978) noted that Americans are motivated to maximize school achievement because of the belief that more education leads to better jobs, higher wages, and social status. Survey-based inquiries have supported the notion that societal conditions affect individuals' achievement via perceptions about the opportunity structure (Ford and Harris 1996;Mickelson 1990). These studies have found that students who express a belief in the achievement ideology (that education leads to status attainment) experience academic success, while those who challenge this belief do not.…”
Section: Centrality Of Beliefs and The Acting White Hypothesismentioning
confidence: 99%
“…Findings indicated that when African American students were asked about their experiences with discrimination, they described hostile relationships with adults in positions of authority including teachers in school (Rosenbloom & Way, 2004 (Ford & Kea, 2009;Ford & Harris, 1996;Hollins & Guzman, 2005). Not surprising then is that African American youths report racially biased treatment within the classroom.…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%
“…Another study highlighted that the disadvantaged high-achieving students establish stronger connections with the school and attach more value to the school compared to the low-achieving ones (Gonzales & Padilla, 1997). While there were some studies asserting that positive attitudes towards school do not affect achievement (Adıgüzel & Karadaş, 2013;Yavuz, 2015), the general tendency in the literature is that it improves achievement (Cheng & Chan, 2003;Ford & Ill, 2008;Lamb & Fullarton, 2002;Malindi & Machenjedze, 2012;OECD, 2003;Tatar, 2006). In fact, the academic achievement of a student who does not like the school and does not like going to the school cannot be expected to be the same as the academic achievement of a student who likes the school, enjoys going to the school, and cares about the school.…”
Section: High-achieving Groupmentioning
confidence: 99%
“…Bir başka çalışmada da, dezavantajlı yüksek başarılı öğrencilerin, düşük başarılara göre okula karşı daha olumlu bağ kurdukları, okula daha çok değer verdikleri vurgulanmaktadır (Gonzales & Padilla, 1997). Okula yönelik olumlu tutumun başarıyı etkilemediğini bildiren çalışmalara rastlanmakla birlikte (Adıgüzel & Karadaş, 2013;Yavuz, 2015) alanyazında genel eğilim başarıyı artırdığı yönündedir (Cheng & Chan, 2003;Ford & Ill, 2008;Lamb & Fullarton, 2002;Malindi & Machenjedze, 2012;OECD, 2003;Tatar, 2006). Esasen okulunu sevmeyen, okula gitmekten hoşlanmayan, bir öğrencinin akademik başarısı ile okulunu seven, okula gitmekten zevk alan, okulu önemseyen bir öğrencinin akademik başarısının aynı olması beklenmez.…”
Section: Tartışma Sonuç Ve öNerilerunclassified